The Comprehensive Systematic Review of Probiotic Interventions and The Gut Lung Axis in Critically ill Patients with Lung Edema - Bayu Anggara H (The International Journal of Medical Science and Health Research, 2026)
Introduction: Critically ill patients with lung edema experience significant morbidity and mortality, with the gut-lung axis emerging as a potential therapeutic target. Probiotic interventions may modulate this bidirectional relationship, but evidence remains conflicting. This systematic review synthesizes evidence on probiotic effects on the gut-lung axis in critically ill adults with lung edema. Methods: A systematic review was conducted following PRISMA guidelines. We screened 200 sources from databases including PubMed, Scopus, and Web of Science (2000-2026). Included studies were randomized controlled trials, cohort studies, and meta-analyses examining probiotic or synbiotic interventions in critically ill adults (≥18 years) with lung edema/ARDS. Primary outcomes included ventilator-associated pneumonia (VAP), mechanical ventilation duration, and gut-lung axis mechanisms. Quality assessment used Cochrane Risk of Bias tools. Results: Forty-eight primary studies and 52 meta-analyses/systematic reviews were included (total N >15,000 patients). Probiotics reduced VAP incidence (RR 0.52-0.75), with synbiotics showing greater efficacy (RR 0.61, 95% CI 0.47-0.80). Mechanical ventilation duration decreased by 1-2.5 days, and ICU length of stay by 1-2 days. Mortality reduction was inconsistent, though severe sepsis subgroups showed benefit (OR 0.38, 95% CI 0.16-0.93). Mechanistically, probiotics improved gut barrier function (reduced lactulose-mannitol ratio, enhanced tight junction proteins), modulated systemic inflammation (IL-6 reduction 140 pg/mL, CRP reduction 72.7%), increased short-chain fatty acid production, and reduced pathogenic colonization. The largest trial (PROSPECT, n=2,653) found no VAP reduction, highlighting context-dependent efficacy. Safety concerns included probiotic bacteremia (1.1% vs 0.1% in PROSPECT). Discussion: Probiotic efficacy is population-specific, with consistent benefits in trauma, surgical, and COVID-19 patients, but minimal effects in general mixed ICU populations receiving contemporary care. Synbiotics, higher doses (≥5×10⁹ CFU/day), and longer duration (≥14 days) optimize outcomes. Methodological quality explains discrepancies between early positive meta-analyses and recent negative trials. Conclusion: Probiotics modulate the gut-lung axis through multiple mechanisms, reducing VAP and ICU stay in selected populations. Routine use in unselected ICU patients is not supported, but targeted therapy in trauma and specific subgroups may be beneficial. Further research should optimize strain selection, dosing, and identify responsive phenotypes.